Effects of Fiscal Policy Shocks in an Open Economy : Evidence from Canada - Belinga, Vincent (World Bank, Washington, DC, 2016)
What is the impact of fiscal policy shocks on key macroeconomic variables in Canada? This question triggered renewed interest in the aftermath of the 2008-09 Great Recession. Indeed, as in many advanced economies, fiscal policy in Canada following the recession started with an expansionary phase to boost domestic demand. It progressed to an adjustment phase to reduce public debt and ensure long-term fiscal sustainability and sustained growth. This paper analyzes the effects of fiscal policy shocks on the Canadian economy, building on the sign-restrictions-VAR approach. Unlike previous studies, this paper explicitly accounts for spillovers from the U.S., Canada's main trading partner, and for oil price fluctuations. The findings show that the size and sign of the spending and tax revenue multipliers depend on whether the analysis controls for the exogenous factors. The tax-cut multiplier varies between 0.2 and 0.5, while the spending multiplier ranges between 0.2 and 1.1; the spending multiplier tends to be larger than the tax-cut multiplier over the past two decades.